(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, applicable law in international arbitration, the theoretical opinions of some scientists about it, the similarities and differences of these theories, the possibilities of the parties to choose applicable law, its application in practice, the problems of online arbitrations and sports arbitrations, as well as, the problems that arise in the application and choice of law and the solutions found based on the relevant international laws and arbitration practice are analyzed.